Treatment of surface water with Moringa Oleifera seed extract and alum – a comparative study using a pilot scale water treatment plant - Muyibi, Suleyman; Alfugara, Akif (Taylor and Francis Group, 2003)
The present study involved the use of a pilot scale water treatment plant to treat turbid surface water from a stream using processed Moringa oleifera seed and alum as primary coagulants. At low initial turbidity of 21.5 to 49.3 NTU, residual turbidities of 2.7, 1.8 and 1.4 NTU were achieved after treatment using Moringa oleifera, alum, and alum with Moringa oleifera as coagulant‐aid, respectively. For medium turbidities varying from 51.8 to 114 NTU, lowest residual turbidities of 2.9, 1.2 and 1.4 were achieved after treatment using Moringa oleifera, alum, and alum with Moringa oleifera as coagulant‐aid, respectively. For high turbidity varying from 163 to 494 NTU, minimum residuals of 1.4, 1.9 and 0.9 NTU were achieved after treatment using Moringa oleifera, alum, and alum with Moringa oleifera as coagulant‐aid, respectively. The proposed mechanism for turbidity removal by Moringa oleifera seed in this study is a combination of partial‐charge neutralization and micro‐bridging or an electrostatic patch mechanism based on the results of zeta potential measurements.